The Impact of Open Access Mandates on Invention - Bryan, Kevin A.; Ozcan, Yasin (The Review of Economics and Statistics, 2021)
Abstract How do barriers to the diffusion of academic research affect innovation? In 2008, the National Institutes of Health (NIH) mandated free online availability of funded research. This policy caused a 50 percentage point increase in free access to funded articles. We introduce a novel measure, in-text patent citations, to study how this mandate affected industry use of academic science. After 2008, patents cite NIH-funded research 12% to 27% more often. Nonfunded research, funded research in journals unaffected by the mandate, and academic citations see no change. These estimates are consistent with a model of search for useful knowledge. Inefficiency caused by academic publishing may be substantial.